2022
DOI: 10.1177/02601060221085809
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of nutritional status among under-five children receiving Integrated Child Development Services (ICDS) in India

Abstract: Background: Undernutrition is a significant public health problem and the leading risk factor for India's disease burden. Aim: To understand the determinants of nutritional status among under-five children receiving Integrated Child Development Services (ICDS) in India. Methods: The study used the National Family Health Survey–4 (2015–16) data. The analysis was carried out for under-five children who have availed of any ICDS services in the 12 months preceding the survey ( n = 1,27,813). Stunting, wasting, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…Our findings reveal reduced undernutrition risk among under-five children in rural areas, contrasting earlier urban-centric studies (Bharati et al, 2008). Rural children benefit from access to fresh, organic and seasonal foods, promoting nutrient-dense intake (Pradhan & Shete, 2022).…”
Section: Utilization Of Icds Servicescontrasting
confidence: 97%
See 3 more Smart Citations
“…Our findings reveal reduced undernutrition risk among under-five children in rural areas, contrasting earlier urban-centric studies (Bharati et al, 2008). Rural children benefit from access to fresh, organic and seasonal foods, promoting nutrient-dense intake (Pradhan & Shete, 2022).…”
Section: Utilization Of Icds Servicescontrasting
confidence: 97%
“…used matching methods and reported improved WAZs among boys aged 0-2 years receiving daily supplementaryfeeding, whereas et al (2018) found no significant association between ICDS services during pregnancy and underweight.With the postreform universality of ICDS access across India, matching methods no longer provide suitable counterfactuals for ICDS beneficiaries due to the role of unobservable self-selection. Thus, observational studies have shown an insignificant and sometimes negative association between ICDS utilization and undernutrition among under-five children in the postreform period(Dixit et al, 2018;Pradhan & Shete, 2022). However, our DID analysis, accounting for preintervention parallel trends, reveals a small but significant correlation between ICDS services and underweight prevalence in 2019-2021 compared to 2015-2016.Although the NFHS data lack explicit information on service quality, it is noteworthy that the Poshan Abhiyaan indicates improvements in quality over the two survey periods.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…The provision of nutrition in AWCs acts as a supplementary source. A recent study (Pradhan & Shete, 2022) based on data from the National Family Health Survey affirms that a sizable proportion of under-five children receiving any ICDS services suffer from undernutrition.…”
Section: Introductionmentioning
confidence: 99%